2016
DOI: 10.22161/ijeab/1.3.32
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermo Chemical Processing on Storability of Sugarcane Juice

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…The result from this study showed that during storage of carrot juice at different temperatures, there was a reduction in total soluble solids (TSS). It could be attributed to the activities of microorganisms that break down sugar in the juices and become acids 42 . In a related study, Kapoor and Aggarwal 40 reported that TSS of tightly corked and pasteurized carrot juice stored at room temperature for 6 months reduced from 10±0.03-9.73±0.11 °Brix.…”
Section: Discussionmentioning
confidence: 99%
“…The result from this study showed that during storage of carrot juice at different temperatures, there was a reduction in total soluble solids (TSS). It could be attributed to the activities of microorganisms that break down sugar in the juices and become acids 42 . In a related study, Kapoor and Aggarwal 40 reported that TSS of tightly corked and pasteurized carrot juice stored at room temperature for 6 months reduced from 10±0.03-9.73±0.11 °Brix.…”
Section: Discussionmentioning
confidence: 99%
“…Energiza o corpo, pois é rico em carboidratos. Ele hidrata o corpo rapidamente quando este é exposto ao calor e à atividade física (KHARE et al, 2012;MATHEW et al, 2016).…”
Section: Benefícios à Saúdeunclassified